INTERACTION OF MODALITY CATEGORY IN RUSSIAN AND UZBEK LANGUAGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the categories of modality in Russian and Uzbek languages through comparative-linguistic and functional-pragmatic analysis. Particular attention is paid to the grammatical nature of the mood category and the semantic-pragmatic essence of modality. Taking into account the typological features of the two languages, the methods of expression, structure, and functional load of the specified categories in speech are analyzed. Furthermore, the relationship between modality and speech acts and communicative strategies is revealed, and their discursive function is defined. The results obtained contribute to identifying similarities and differences in the categories of mood and modality in Russian and Uzbek languages.